rules-of-inference
rules-of-inference
3. Distribute A ∨ (𝐵 ∧ 𝐶) ≡ (𝐴 ∨ 𝐵) ∧ (𝐴 ∨ 𝐶)
Step 2: Each premise is now a conjunction of one or more
clauses. Write each clause on a separate line.
Step 3: Apply resolution rule by taking two clauses which
contain the same atom with opposite signs.
Step 4: We continue until we get both a proposition, and its
negation, so that we can resolve these together to
get the empty clause.
Example1: Using resolution rule prove
𝑝 ∨ 𝑞, 𝑝 → 𝑟, 𝑎𝑛𝑑 𝑞 → 𝑠 ∴ r∨ 𝑠
Ans. I.Convert the premises to normal form and write them on
separate lines.
𝐶1: p∨ 𝑞
𝐶2: ¬𝑝 ∨ 𝑟
𝐶3 : ¬𝑞 ∨ 𝑠
II. Negate the conclusion and convert it to the normal form
¬(𝑟 ∨ 𝑠) ≡ ¬𝑟 ∧ ¬𝑠
𝐶4: ¬𝑟∧ ¬𝑠
𝐶5: ¬𝑟
𝐶6: ¬𝑠
III. Deduce the clause by resolution
𝐶7: ¬𝑃 𝑓𝑟𝑜𝑚 𝐶2 𝑎𝑛𝑑 𝐶5
𝐶8: 𝑞 𝑓𝑟𝑜𝑚 𝐶1 𝑎𝑛𝑑 𝐶7
𝐶9: ¬𝑞 𝑓𝑟𝑜𝑚 𝐶3 𝑎𝑛𝑑 𝐶6
𝐶10: ◻ 𝑓𝑟𝑜𝑚 𝐶8 𝑎𝑛𝑑 𝐶9
Hence the argument is correct.
Example 2: By resolution rule prove
~ (p∧~q), (~q∨r), ~r ⊢ ~p
∃𝑥(𝑃(𝑥) ∧ ¬𝐵(𝑥))
Step Reason
∃𝑥(𝐶(𝑥) ∧ ¬𝐵(𝑥)) Premise
C(a) ∧ ¬𝐵(𝑎) Existential instantiation from1
3.C(a) Simplification from 2
4¬𝐵(𝑎) Simplification from 2
5∀𝑥(𝐶(𝑥) → 𝑃(𝑥)) Premise
6C(a) → 𝑃(𝑎) Universal instantiation from 5
7P(a) Modus ponens from 3and 6
8P(a)∧ ¬𝐵(𝑎) Conjunction from 7and 4
9∃𝑥(𝑃(𝑥) ∧ ¬𝐵(𝑥)) Existential generalization
from 8
Example : Show that the premises “All fish can swim” and
“Eel is a fish” imply the conclusion “Eel can swim”
Ans. Let F(x) denote ‘x is a fish’,S(x) denote ‘x can swim’. ∴the
premises are ∀𝑥(𝐹(𝑥) → 𝑆(𝑥)) and F(Eel). The conclusion is
S(Eel).
Step Reason
1. ∀𝑥(𝐹(𝑥) → 𝑆(𝑥)) 𝑃𝑟𝑒𝑚𝑖𝑠𝑒
2. F(Eel)→ 𝑆(𝐸𝑒𝑙) 𝑈𝑛𝑖𝑣𝑒𝑟𝑠𝑎𝑙 𝑖𝑛𝑠𝑡𝑎𝑛𝑡𝑖𝑎𝑡𝑖𝑜𝑛 𝑓𝑟𝑜𝑚
1
3 F(Eel) Premise
4. S(Eel) Modus ponens from 2and 3
Example : Express A ↔ 𝐵 𝑖𝑛 disjunctive normal form
Ans. 𝐴 ↔ 𝐵 ≡ (𝐴 → 𝐵) ∧ (𝐵 → 𝐴)
≡ (¬𝐴 ∨ 𝐵) ∧ (¬𝐵 ∨ 𝐴)
≡ ((¬𝐴 ∨ 𝐵) ∧ ¬𝐵) ∨ ((¬𝐴 ∨ 𝐵) ∧ 𝐴)
≡ (¬𝐴 ∧ ¬𝐵) ∨ (𝐵 ∧ ¬𝐵) ∨ (¬𝐴 ∧ 𝐴) ∨ (𝐵 ∧ 𝐴)
≡ (¬𝐴 ∧ ¬𝐵) ∨ 𝐹𝑎𝑙𝑠𝑒 ∨ 𝐹𝑎𝑙𝑠𝑒 ∨ (𝐵 ∧ 𝐴)
≡ (¬𝐴 ∧ ¬𝐵) ∨ (𝐵 ∧ 𝐴)
Example : Obtain the disjunctive normal form of
(𝑝 → 𝑞) ∧ ¬𝑞 ≡ (¬𝑝 ∨ 𝑞) ∧ ¬𝑞